2020
DOI: 10.1177/0963689720929992
|View full text |Cite
|
Sign up to set email alerts
|

SDF-1/CXCR4 Augments the Therapeutic Effect of Bone Marrow Mesenchymal Stem Cells in the Treatment of Lipopolysaccharide-Induced Liver Injury by Promoting Their Migration Through PI3K/Akt Signaling Pathway

Abstract: Mesenchymal stem cells (MSCs) are thought to have great potential in the therapy of acute liver injury. It is possible that these cells may be regulated by the stromal cell-derived factor-1 (SDF-1)/CXC chemokine receptor-4 (CXCR4) signaling axis, which has been shown to promote stem cells migration in the inflammation-associated diseases. However, the effects of SDF-1/CXCR4 axis on the MSCs-transplantation-based treatment for acute liver injury and the underlying mechanisms are largely unknown. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Endotoxin, an important pathogenic factor causing sepsis, stimulates monocytes to produce a variety of proinflammatory factors, thus releasing inflammatory factors through a series of phosphorylation pathways. These inflammatory factors further prompt the release of inflammatory mediators and the generation of hydrolase and oxygen-free radicals, leading to typical symptoms of sepsis such as pathological coagulation, vasodilation, and organ dysfunction [ 18 21 ]. All these results indicated that oxymatrine plus antiviral therapy could effectively reduce the levels of endotoxin and inflammatory reactions in patients and protect organ function.…”
Section: Discussionmentioning
confidence: 99%
“…Endotoxin, an important pathogenic factor causing sepsis, stimulates monocytes to produce a variety of proinflammatory factors, thus releasing inflammatory factors through a series of phosphorylation pathways. These inflammatory factors further prompt the release of inflammatory mediators and the generation of hydrolase and oxygen-free radicals, leading to typical symptoms of sepsis such as pathological coagulation, vasodilation, and organ dysfunction [ 18 21 ]. All these results indicated that oxymatrine plus antiviral therapy could effectively reduce the levels of endotoxin and inflammatory reactions in patients and protect organ function.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, our results suggest that SDF-1/ /CXCR4 activates JAK2/STAT3 to regulate the osteogenic differentiation of BMSCs; however, there are still some shortcomings in this study. Xiu et al [31] confirmed that SDF-1/CXCR4 can promote the migration of BMSCs and enhance SDF-1/CXCR4 therapeutic effect of BMSCs in LPS-induced acute liver injury, which is caused by the activation of the PI3K/ /Akt signaling pathway. Therefore, it is important to study the effect of SDF-1/CXCR4 on other aspects of BMSCs function, including their migration.…”
Section: Discussionmentioning
confidence: 97%
“…Currently, mesenchymal stem cells (MSCs) from different sources are considered to have enormous potential in the treatment of acute liver injury ( Deng et al, 2014 ; Xiu et al, 2020 ). These cells need to migrate to the injury sites to function, which may be regulated by the CXCL12/CXCR4 signaling axis.…”
Section: The Protective Effect Of Cxcr4 Signaling Pathway In Acute Liver Injury and Regenerationmentioning
confidence: 99%
“…Interestingly, overexpression of CXCR4 in BMSCs can substantially promote their migration and result in even better therapeutic effects for acute liver injury. This may be attributed to the activation of PI3K/Akt signaling pathway in BMSCs that is downstream of CXCR4 ( Xiu et al, 2020 ). The CXCL12/CXCR4 axis similarly regulates the migration of umbilical cord-derived mesenchymal stem cells (UC-MSCs) to the injured liver.…”
Section: The Protective Effect Of Cxcr4 Signaling Pathway In Acute Liver Injury and Regenerationmentioning
confidence: 99%